Gambaran Penyesuaian Diadik pada Pasangan Dewasa Muda di Awal Pernikahan - Pingkan C. B. Rumondor (Bina Nusantara University, 2011)
Marriage is one of young adulthood’s developmental task. The beginning phase of marriage is often beyond expectation of the newlyweds, it is a hard adjustment time for the couples. Therefore, adjustment in this phase is crucial for future marriage quality. The aim of this research is to describe the dyadic adjustment of young adult couples in the beginning phase of their marriage, using Spanier’s dimension of dyadic adjustment. This reasearch use qualitative approach with interview and observation as data collection method. This research found that in dyadic consensus, one couple see a disagreement because of different way of thinking. In dyadic cohesion, one couple feel that they are lack of intimacy. In dyadic satisfaction, the couples tend to feel satisfied. While in affectional expression, the couples tend to express affection thruouh physical contact and behaviour that accord with their couple’s preference. Areas that could be improved are couple’s communication to reach dyadic concensus and couple’s intimacy to increase dyadic cohession.